The Consent of Husband for Khul‘ in Islamic Law and Pakistani Legal System: A Comparative Study with Specific Reference to Case Law: - Siddique, Hafiz (Al Basirah, 2023)
The issue of the husband’s consent for khul‘ is debatable among classical and contemporary Muslim jurists. The judiciary of Pakistan has played its role to decide the controversy between husband and wife in the cases of khul‘. It is evident in Islamic law that a husband can dissolves the marriage and divorce his wife by denoting the word talaq. There is no need for justification of divorce from the husband neither in Islamic law nor the Pakistani legal system. But the female initiative divorce is debatable and depends on the consent of the husband to some Muslim jurists while others oppose this view. The Pakistani judiciary is also not on the same page, various judgments and different interpretations by the judges. In Pakistani law, The Dissolution of Muslim Marriage Act 1939 in its section 2 mentions certain justified reasons for the dissolution of marriage by a woman but it’s not easy to justify the reason in a court of law. This paper tries to find whether the consent of the husband is mandatory in khul‘ case or not. It denotes the opinions of classical and contemporary Muslim jurists. This research examines the grounds for the dissolution of marriage in Islamic law and the Pakistani legal system. The role of the Pakistani judiciary will be investigated and compared with the principles of Islamic law regarding the consent of the husband in khul‘. This research concludes that the husband’s approval and consent is neither required in Islamic law nor in the Pakistani legal system.